Comparison of the molecular structure of heat and pressure-treated corn starch based on experimental data and molecular dynamics simulation. (April 2022) - Liu, Zhenyu; Fu, Yongxia; Zhang, Fan; Zhao, Qingyu; Xue, Yong; Hu, Jinrong; Shen, Qun
Abstract: The effect of high hydrostatic pressure (HHP) and heating on the molecular structure of corn starch were firstly studied using classical experimental methods and molecular dynamics (MD) simulation. Heat-treated (HT) starches showed more amorphous content further than pressure-treated (PT) starches at similar DGs, further confirming that a higher level of gelatinization occurred after heating. Compared with PT starches, longer external B2 and B3 chains (DP > 25) degraded more into A chains (DP 6–12) in HT samples at a similar degree of gelatinization (DG). Heating increased the breakage of α-1, 4-glycosidic bonds and significantly reduced molecular weights even one third of the native corn starch at 100% DG. On the other hand, MD results showed that HHP triggered a greater number of amylose-water inter-molecular hydrogen bonds which agreed well with the higher the freedom degree of water molecules in PT starches. Regarding to various energy changes, PT starches exhibited lower bonding-related energies, but higher Van der Waals and electrostatic forces than HT ones. This study adds to understanding of the different molecular features of heating and HHP gelatinization and provides a molecular tool to assist the starch industry in selecting better modification parameters. Graphical abstract: Image 1 Highlights: Heating and HHP-induced changes on corn starch molecular structure are examined. Longer external B2 and B3 chains degraded more into A chains in HT samples compared with PT starches. The α-1, 4-glycosidic bonds were preferentially broken and thus reduced molecular weights during heating gelatinization. HHP triggered a greater number of amylose-water inter-molecular hydrogen bonds. MD simulation provided various explanations of energy changes during heating and HHP gelatinization.